Workshop on Giving, Receiving, and Soliciting Feedback - Jeff Pettit (Association of American Medical Colleges, 2011)
Abstract Introduction Providing effective feedback is an important component of medical education. This workshop was created for faculty, residents, and medical students from an exhaustive review of medical and business literature focusing on how to give, receive, and solicit feedback that is both informative and participative. Methods This workshop takes approximately 90 minutes. The workshop contains a PowerPoint lecture, role-playing exercise, and reflective exercises regarding feedback. Results The topic was requested by the 90 representative members of the community teaching scholars program at the Carver College of Medicine. In addition, this workshop has been presented to six regional community teaching scholars campuses around the state of Iowa; several different resident programs at the University of Iowa Hospitals & Clinics; and two regional AAMC Group on Educational Affairs meetings. Discussion The widespread interest in this workshop, demonstrates the importance of providing formal training in providing effective feedback and this workshop provides an engaging format for this formal training.